Differential discontinuation by covert use status in Kenya - Dana Sarnak; Shannon N. Wood; Phil Anglewicz; Elizabeth Gummerson; Peter Gichangi; Mary Thiongo; Caroline Moreau (Elsevier, 2023)
Objectives: Qualitative research suggests that covert users may be more likely to discontinue contraception due to the logistics of discretion and fear of disclosure. This study sought to quantify whether covert users are more likely to discontinue contraception than overt users. Study design: We used a national longitudinal survey from Kenya conducted from November 2019/February 2020 to November 2020/April 2021 to test whether the time to discontinuation between covert and overt users still in need of contraception differed using survival analyses over a period of 5 years since method initiation. Results: Multivariate Cox regression results showed there was an interaction with time and covert use on the risk of discontinuation; for every additional month of use, there was an increased risk of discontinuation of covert users compared to overt users (3% increased hazard, p = 0.02). At 1 and 2 years, there were no differences in the hazard of discontinuation (adjusted hazard ratio [aHR]1 year 0.95, 95% CI 0.54-1.65 and aHR2 years 1.37, 95% CI 0.85-2.21), yet at 3, 4, and 5 years, the hazard of discontinuation was higher for covert compared to overt users (aHR3 years 1.99, 95% 1.11-3.56; aHR4 years 2.89, 95% CI 2.0-6.40; aHR5 years 4.18, 95% CI 1.45-12.0). Conclusions: These results suggest efforts are needed to support covert users in managing their contraceptive use and for improving contraceptive counseling surrounding covert use. Our findings shed light on the increasing challenge covert users face after approximately the first 2 years of use; covert users require additional follow-up in both research and care provision. Implications: Covert users are at a higher risk of discontinuation of contraception while still trying to avoid pregnancy, particularly after the first 2 years of use. Family planning providers and programs must protect access to and maintain the privacy of reproductive services to this population, focusing on follow-up care provision and counseling.